Efforts to solve the waste water treatment issues in palm oil industry - Murakami, M.; Andou, Y.; Shirai, Y. (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Palm oil industry is main industry in Southeast Asia. Although palm oil can be great profitable, it can cause generation of methane gas as green house effect. In order to clarify what has happen in lagoon at upstream under the anaerobic lagoon method, we will consider the mechanism relate to generate scum in lagoon.